Papo de bicho: análises multimodais de interações entre humanos e seus animais de estimação - Gallina, Rafael Fernandes (Universidade do Vale do Rio dos Sinos, 2020)
The communication among animals and human beings has been studied in many fields of knowledge such as Biology, or, more specifically, on the field of Animal Communication (BRADBURY; VEHRENCAMP, 2011; KENDRICK et al, 2018), the Human Health, especially on the fields of Psychiatry and Psychology (BURES et al, 2014; MATCHOCK, 2015) and on Linguistics, both through a cognitivist approach (ZUBERBÜHLER, 2015) as well as interactional (MONDÉMÉ, 2016; MONDÉMÉ, 2018; TANNEN, 2004). This research is inserted on the scope of this last research area. Supported by the theoretical-methodological assumptions of Conversation Analysis this study is dedicated to describing and analyzing moments of coexistence among human beings and their pets in their environments in which they cohabit. We seek to: (a) Identify organizational aspects of interactions among human and non human animals, focusing on how these interactions are coconstructed sequentially; (b) Perform multimodal analysis of interactions among human and non-human animals, observing the resources used by the participants to reach intersubjectivity; (c) Verify if multimodal analysis offers resources to reach an understanding of how the interactions among human and non-human animals are realized. To do so, I resort to three interactions between humans and their respective pets through the perspective of Conversations Analysis (SACKS, 1992; SCHEGLOOF, 2007; SACKS, SCHEGLOOF, JEFFERSON, 1974). The interactions analyzed were recorded in audio and video format and transcribed according to the conventions of the Jeffersonian transcription system (BOLDEN; HEPBURN, 2017), for the spoken data, and the multimodal transcription system developed by Mondada (2016), for the data composed by embodied actions. The results from the analysis of the data show that: (i) humans and nonhuman animals engage in activities which require joint attention and are shown to act reflexively one in relation to the other; (ii) the interactions here analyzed are organized in sequences, constituted of adjacency pairs occupied by turns-at-talk or embodied actions; (iii) the alignment/disalignment phenomena are present on the interactions.
Keywords: Análise da conversa; Análise multimodal; Interações entre animais humanos e animais não humanos; Conversation analysis; Interactions among human and non-human animals; Multimodal analysis